Language Politeness in Javanese and Sundanese Border Cultural Landscapes in Elementary School Student Learning - Andini, Siti; Sudarto, Sudarto; Ayatullah, Ayatullah; Farhan, Hamid Mohamad (Journal of Innovation in Educational and Cultural Research, 2025)
Language politeness plays a crucial role in maintaining harmony and effectiveness of communication, especially for elementary school students in cultural border areas. This study aims to understand the application of language politeness in the elementary education environment in the Java-Sunda border area. This study uses a qualitative method with a descriptive phenomenological approach to describe the phenomenon of language politeness in learning in grade 5 of SD Negeri Waringinsari and SD Negeri Bener. Data were collected through observation and recording of oral speech between students and teachers during the learning process, which were then analyzed using interactive data analysis techniques. The results showed that the principles of language politeness, formulated by Geoffrey Leech, were well applied by teachers and students in classroom interactions. Applying the principles of proverbs, Wisdom, Generosity, Respect, Simplicity, Agreement, and Sympathy proved effective in creating an inclusive and harmonious learning environment. In addition, the use of mixed language between Indonesian and local languages in classroom communication reflects adaptation to the local cultural context, which helps strengthen the emotional connection between teachers and students. Language politeness is important to maintain effective communication, build positive social relationships, and prevent conflicts that may arise due to cultural differences.